Calamagrostis altaica, a neglected species of the Chinese flora with notes on C. korotkyi (Poaceae, Agrostidinae) - Paszko, Beata; Chen, Wen-Li; Liu, Bing (Phytotaxa, 2016)
Calamagrostis altaica, a forgotten name in Chinese Poaceae and formerly known only from the Chinese part of the Mongolian Altai, is reported to be the correct name for most of the gatherings from the northern part of Xinjiang, which are ascribed to Deyeuxia korotkyi and D. pyramidalis in Flora of China. Calamagrostis altaica is reported from the Kazakh Altai and the Chinese part of the Tarbagatai Range for the first time. In China C. korotkyi is restricted to Heilongjiang and Inner Mongolia. The taxonomy of C. altaica is clarified and discussed, especially in relation to the morphologically similar C. arundinacea and C. korotkyi. Amended circumscriptions of C. altaica and C. korotkyi are given, together with illustrations of their spikelet and culm morphology and notes on their identification. The entire range of C. altaica and the Chinese distribution of C. korotkyi are described.